Graphic standards field guide to hardscape - Hopper, Leonard J. (Hoboken, N.J. : John Wiley & Sons, 2010)
'Part of Wiley's new Graphic Standard Field Guides series, Graphic Standards Field Guide to Hardscape is the reference for the on-the-go professional. The perfect companion to the main Landscape Architectural Graphic Standards, this field guide provides the same standard architectural details and drawings that professionals count on from Graphic Standards, and adds photographs and interpretive information that are essential when outside the office and away from the design desk. The small trim size and durable binding makes it easy for landscape architects and designers to keep this resource on hand when on site, at meetings, or with clients. Organized to follow CSI's MasterFormat, this handy reference helps the landscape architect address a wide variety of practical issues pertaining to hardscape including site work, bases and paving, site improvements, furnishing and equipment, and services. A procedural checklist makes sure nothing's missed on site'--
Includes index.
Keywords: Landscape construction -- Designs and plans -- Standards; Garden structures -- Designs and plans -- Standards